Synthesis, Modification and Characterization of New Phenolic Resins linked to Tetrabromophthalimide - Hasan, Mustafa Salah; AL-Azzawi, Ahlam Marouf (Iraqi Journal of Science, 2023)
The present work aimed to synthesize new phenol resins via incorporation of structural modification through introducing new phenolic compounds containing cyclic imide moiety in reaction with formaldehyde. The synthesis of these new resins involved three steps. First, one of the three N-(hydroxyphenyl)tetrabromophtalamic acids 1-3 were processed via a reaction between tetrabromophthalic anhydride and aminophenols. Amic acids 1-3 were dehydrated in the second step by smelting, producing the identical N-(hydroxyphenyl)tetrabromophthalimides 4-6. The new imides represent the new phenolic component that was presented in condensation reaction with formaldehyde in the third step, creating the target phenolic resins 7-9. The work also involved curing the new resins through esterification of phenolic OH groups by treatment with benzoyl chloride. The chemical structures of prepared compounds were confirmed according to FT-IR, 1H NMR, and 13C NMR spectral data. As a conclusion, the present work supply of new phenolic resins and the presence of the cyclic imide (tetrabromophthalimide) moiety in their structures exhibit high softening points and resistance to solubility, which fit with some applications, while subsequent curing through esterification exhibits better solubility and lower softening points, which fit with other applications.